Antimicrobial Activities of Ferrocenyl Complexes: A Review - Ashraf S. Hassan, Taghrid S. Hafez (Journal of Applied Pharmaceutical Science, 2018)
Bioorganometallic chemistry was devoted to the synthesis of new organometallic compounds and their biological and medicinal activities. Ferrocenyl complexes display various pharmacological intÐµrests such as antibacterial and antifungal activities. This review article will focus on antimicrobial activities of ferrocenyl complexes (Cu, Co, Ni, and Zn).
Keywords: Ferroc&ETH; µne compounds, Metal complexes, Ferrocenyl complexes, Antimicrobial agents.